Penguatan Minat dan Motivasi Belajar Siswa Sekolah Dasar melalui Kegiatan Bimbingan Belajar di Dompak Seberang - Azizah Demokratia Adilah; Deni Dwi Pradana Hermansyah; Restu Prasetyo Andriyatno; Elsa Nursyifa Hasan; Farhan Adyatma Zachary; Irma Ariyanti; Luqman Hakiki; Maria Maria; Merry Dwi Afrillina; Dios Sarkity (BADAN PENERBIT STIEPARI PRESS, 2025)
This community service program was carried out with the aim of enhancing the interest and motivation of elementary school students in Dompak Seberang through creative tutoring activities. The program involved 25 students from grades I–VI at SDN 008 Bukit Bestari, accompanied by 19 KKN (student community service) participants. To address the challenges faced, an alternative approach was needed—one that was more creative, enjoyable, and able to stimulate active student engagement. One such effort implemented was tutoring activities based on the concept of fun learning. The method used was qualitative descriptive with a participatory approach through observation, interviews, and student satisfaction questionnaires. Activities were conducted twice a week, focusing on core subjects such as Mathematics, English, and literacy-numeracy (reading, writing, and arithmetic). The learning strategies applied included the expository method, fun learning, ice breaking, and simple rewards. The implementation of the Creative Tutoring Program at SD Dompak Seberang produced several important findings based on direct observations, documentation, and the results of student satisfaction surveys. The survey showed that 100% of students enjoyed learning in the tutoring sessions, 96% stated that the classroom atmosphere made them more enthusiastic, and 100% expressed interest in participating in similar activities again. Field observations also revealed improvements in students’ activeness, confidence in asking questions, and participation in discussions. Thus, the creative tutoring activities proved effective in strengthening students’ learning interest and motivation and can serve as a sustainable community service model that is replicable in other regions.